Flocking Bird Strikes on Engine Fan Blades and Their Effect on Rotor System: A Numerical Simulation - Bin Wu; Jiewei Lin; Anshun Xie; Ning Wang; Guichang Zhang; Junhong Zhang; Huwei Dai (Aerospace, 2022)
Bird strikes are a common, serious, and devastating event in aviation accidents, and multi-bird strikes are also frequently reported. A numerical multi-bird-strike simulation was performed to investigate the effect of flocking birds striking on engine blades. The smooth particle hydrodynamics (SPH) method was adopted in the hemispherical-ended bird substitute model, and the finite element method (FEM) with EOS state equation was adopted for the fan model as well. Impact analyses have been presented using different flocking birds and impact location distributions. A “0-2-1” supported rotor system dynamic model was established to study the effect of the multi-bird-strike impact forces on the rotor system. The results show that bird-strike severity is related to the impact location distribution, with blade-root impacts being the most dangerous. The small flocking bird strikes had little effect on the fan compared to the cases of medium flocking birds and the large single bird. The dynamic response of the fan to the small flocking birds was the same as without a bird strike, while the other cases changed the motion period and excited the rotor first-order vibration.